IDENTIFICATION AND CALCULATION OF HOUSEHOLD INCOME SOURCES OF SHRIMP CRACKER BUSINESS ACTORS IN SUNGSANG I AND II VILLAGES, BANYUASIN II DISTRICT - Noverdila, Noverdila; Adriani, Dessy; Purbiyanti, Erni (Jurnal Perikanan Unram, 2025)
Sungsang I and Sungsang II Villages are tidal areas because they are located on the coast and directly adjacent to the Bangka Strait, Sungsang I and Sungsang II Villages are one of the areas that have abundant marine products in Banyuasin II Regency, one of which is shrimp which is then processed by the local community into crackers in the home industry. Until now, there has been little socio-economic research on the identification and calculation of the source of household income of shrimp cracker business actors in this region. The purpose of this study is to calculate the amount of contribution of each source of income to the total household income of shrimp cracker business actors and provide an overview of household economic dependence on the shrimp cracker business as the main or additional livelihood. The methods used in this study are quantitative and qualitative methods with a descriptive approach, which aims to analyze the cost, revenue, and income of shrimp cracker business in Sungsang I and Sungsang II Villages. The analysis was carried out using the formula for calculating production, fixed costs, variable costs, and household business income. The results of this study show that the income of the cooked shrimp cracker business is Rp 2,774,533 per month with a total revenue of Rp. 4,420,000 per month and the income of the raw shrimp cracker business is Rp. 1,332,226 per month with a total revenue of Rp. 4,420,000 per month, which means that the shrimp cracker business in Sungsang I and Sungsang II Villages is feasible to run.